Navigating the green shift with innovative techniques in petrochemical emission control - Muhammad Ahsan; Lixin Tian; Ruijin Du (Scientific Reports)
Abstract This analysis delves into the profound influence of the petrochemical sector on carbon emissions, highlighting the insufficient data that impedes the formulation of effective emission reduction strategies. By concentrating on the unique challenges within this industry, the study employs a sophisticated decision-making model to explore the complex interconnections between carbon emissions, mitigation approaches, and investment choices. The primary objectives include boosting energy efficiency, refining CO2 reduction initiatives, and cutting associated costs. To navigate the intricacies of carbon footprint assessment, the research introduces a novel hybrid framework that merges scientific modeling with a code-based prototype to aid in strategic planning. The efficacy of this approach is validated by experts, demonstrating its versatility and adaptability through CNHS mapping, which enables the customization of emission reduction strategies across different scenarios.